Estimating the Fiscal Multiplier in Argentina - Anos-Casero, Paloma; Cerdeiro, Diego; Trezzi, Riccardo (2012)
Argentina's government has resorted to fiscal policy as a countercyclical tool to mitigate the negative impact of the current economic downturn on aggregate demand. Empirical results based on a vector error correction model suggest, however, that the fiscal multiplier is relatively small and short-lived. This could reflect a number of factors, including the higher propensity of households to save during the economic downturn, the implementation lag of public expenditures, particularly of capital expenditures, and the narrow tax base that limits the impact of countercyclical revenue measures on domestic demand.